Amphiphilic-molecular templated porous β-MnO2 for high-performance rechargeable aqueous Zn-MnO2 batteries. (20th August 2022) - Huang, Jing; Han, Mei; Ji, Peng; He, Bo; Feng, Xuansheng; Han, Ying; Gao, Kesheng; Miao, Zeqing; Sun, Changlong; Zhi, Jian; Zhang, Lei; Chen, P.
Abstract: Compared with Li-ion batteries, rechargeable aqueous Zn-ion batteries (RAZIBs) offer energy storage with low cost and good safety. Nevertheless, the irreversible structural transformations and retarded reaction kinetics that always accompany manganese-based materials, which directly lead to low capacity and poor cycling stability, substantially hinder their practical application in large-scale energy storage. Herein, the introduction of mesopores in β-MnO2 cathode is demonstrated to be effective in solving the above problems, by employing poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) template (P123) as pore-forming agent. The assembled porous β-MnO2 /Zn full battery delivered a highly reversible capacity of 333 mAh g −1 under 0.1 A g −1, superior capacity retention of 88% after 1000 cycles under 1.0 A g −1 and great rate capability (87 mAh g −1 at 2 A g −1 and 56 mAh g −1 at 3 A g −1 ). In addition, the structural evolution of porous MnO2 during cycling, as well as the impact of template concentration on the pore structures, is further studied. A novel strategy for optimizing the electrochemical performance of RAZIBs is provided by this structural modulation strategy.